The effect of apolipoprotein E polymorphism on serum metabolome - a population-based 10-year follow-up study - Karjalainen J-P.; Mononen N.; Hutri-Kähönen N.; Lehtimäki M.; Juonala M.; Ala-Korpela M.; Kähönen M.; Raitakari O.; Lehtimäki T. (NATURE PUBLISHING GROUP, 2022)
Apolipoprotein E (apoE) is the key regulator of plasma lipids, mediating altered functionalities in lipoprotein metabolism - affecting the risk of coronary artery (CAD) and Alzheimer's diseases, as well as longevity. Searching pathways influenced by apoE prior to adverse manifestations, we utilized a metabolome dataset of 228 nuclear-magnetic-resonance-measured serum parameters with a 10-year follow-up from the population-based Young Finns Study cohort of 2,234 apoE-genotyped (rs7412, rs429358) adults, aged 24-39 at baseline. At the end of our follow-up, by limiting FDR-corrected p < 0.05, regression analyses revealed 180/ 228 apoE-polymorphism-related associations with the studied metabolites, in all subjects - without indications of apoE x sex interactions. Across all measured apoE-and apoB-containing lipoproteins, e4 allele had consistently atherogenic and epsilon 2 protective effect on particle concentrations of free/esterified cholesterol, triglycerides, phospholipids and total lipids. As novel findings, epsilon 4 associated with glycoprotein acetyls, LDL-diameter and isoleucine - all reported biomarkers of CAD-risk, inflammation, diabetes and total mortality. ApoE-subgroup differences persisted through our 10-year follow-up, although some variation of individual metabolite levels was noticed. In conclusion, apoE polymorphism associate with a complex metabolic change, including aberrations in multiple novel biomarkers related to elevated cardiometabolic and all-cause mortality risk, extending our understanding about the role of apoE in health and disease.